Monitoring of pollution factors of solidified body leachate in a drilling well site and its influence on the surface water environment - Zhikun Liu (IWA Publishing, 2021)
Aiming at the pollution of the leaching solution of the solidified body in the wellbore, a water eutrophication level evaluation algorithm based on the optimized analytic hierarchy process is proposed from the current situation of many factors affecting the eutrophication of the water body and the difficulty of evaluation. Based on this, the user-oriented PC software monitoring system was developed, which mainly includes three major modules: surface water environment monitoring, water eutrophication evaluation, water bloom prediction and warning, and system assistance. The surface water environment monitoring module can receive and display the surface water environment parameter information in real time, and has the functions of data comparison analysis and historical data search, and the eutrophication assessment and water bloom prediction and warning module can analyze the eutrophication status of water bodies in real time and provide short-term and medium-term warnings for water blooms. This research can promote the control of the leachate pollution of the wellbore in the wellbore and the optimization of the surface water environment. HIGHLIGHTS Propose a water eutrophication level evaluation algorithm.; Develop a user-oriented PC software monitoring system.; The research can promote the control of the leachate pollution of the wellbore in the wellbore.; The research can promote the optimization of the surface water environment.; The water bloom prediction and warning module can analyze the eutrophication status of water bodies in real time.;